FORMALIZATION ORGANIZATIONAL-TECHNOLOGICAL SYSTEM CONTROL LIFE CYCLE OF AEROTECHICS - Тамаргазін, О.; Ліннік, І.; Олег, М. (Science-based technologies, 2011)
In the article basic attention is spared design and realization of systems approach in relation to the problem of increase of efficiency and quality of aerotechics due to forming of system morphology of management of it’s life cycle. The offered method is intended for creation informatively compatible technical, structurally organization-al, functional and programmatic methodical facilities, which are realize the production processes of design, manufacture and maintenance, on the unique methodological and logical-information basis. This is especially important from the point of view to that efficiency of introduction media on all stages of life cycle of aerotechics is provided due to integration of the information-voluntary systems, which provides the system complexing of au-tomation systems of the different functional setting.